PENGARUH TIME PRESSURE, PROFESIONAL COMMITMENT DAN LOCUS OF CONTROL TERHADAP PENGHENTIAN PREMATUR PROSEDUR AUDIT - I Putu Gede Krisna Ekadana; Ni Komang Sumadi (UNHI Press, 2021)
Premature sign off audit procedures is a condition where the auditor stops one or more audit steps required in the audit procedure without replacing other steps. This study aims to examine how the effect of time pressure, professional commitment, and locus of control on premature termination of audit procedures. The population in this study is a public accounting firm in Bali Province. This type of research is quantitative and the sampling technique used is purposive sampling method, so that the sample obtained is as many as 40 auditors. The analytical method used in this research is multiple linear regression analysis. The hypothesis was tested using the t-test with a significance level of 5%. Based on the results of the simultaneous analysis test, time pressure, professional commitment, and locus of control have a significant effect on premature termination of audit procedures, and partially time pressure, professional commitment, and locus of control have a positive and significant effect on premature termination of audit procedures.